Does independent director’s cash compensation matter? Evidence from corporate fraud - Radwan, Alkebsee; Tian, Gaoliang; Garefalakis, Alexandros; Koutoupis, Andreas; Kyriakogkonas, Panagiotis (Journal of Business Economics and Management, 2022)
This study empirically investigates the relationship between independent directors’ cash compensation and the likelihood of corporate fraud. Using data of 2542 Chinese firms and 17239 firm years from 2010 to 2017, the findings of logistic regression, firm-fixed effects, instrumental variable specification, and propensity score matching models show that there is a negative association between cash compensation of independent directors and corporate fraud. Our findings suggest that if independent directors are treated with higher cash compensation, it enhances the board’s independence and makes the effective monitoring over management behaviors and financial reporting process. On contrary to non-SOEs, the findings also document that the negative association between independent directors’ compensation and corporate fraud is pronounced in SOEs. The study not only shows the impact of independent director’s compensation on firm fraud beyond agency and contract theories but also creates policy implications regarding independent director’s compensation in particular scenario of emerging economies.